Dentists' restorative decision‐making and implications for an 'amalgamless' profession. Part 4: clinical factor. (28th June 2017) - Alexander, G; Hopcraft, MS; Tyas, MJ; Wong, RHK
Abstract: Background: The Minamata Convention embodies a worldwide reduction in the production and use of mercury and mercury‐containing products and processes, including a phase‐down of dental amalgam. This will change the approach to the use of direct restorative materials in the near future. There is little research as to the influence of clinical factors on dentists' decision‐making which may be of use when determining the impact of any change. Methods: An online survey relating to aspects of and attitudes to the use of direct restorative materials was distributed to all dentists who were members of the Australian Dental Association and/or members or fellows of the Royal Australasian College of Dental Surgeons. Data were statistically analysed. Results: There were 408 respondents to the survey. Eighty‐seven per cent of respondents (strongly) disagreed that amalgam was a technically more difficult material to place compared with resin composite, 82% (strongly) disagreed that placement time for amalgam was longer than that for resin composite and 69% (strongly) disagreed that amalgam was more difficult to finish than resin composite. Eighty‐three per cent of respondents stated they were confident in their ability to place amalgam restorations. Where physical properties were of importance, indirect restorations were preferred (e.g. parafunction) 54%. The factors considered most important when choosing a direct restorative material included moisture control and aesthetics; least important factors were cost and time to place. Conclusions: There is consensus that amalgam is not more technically difficult to use, place or finish than resin composite and vice versa. There is recognition that both amalgam and resin composite have limitations in terms of physical properties. When choosing a direct restorative material, clinical factors considered to be of greatest importance are moisture control, aesthetics and the need to apply minimally invasive approaches. There is little difference in the opinions of users and non‐users of amalgam with respect to these findings.